Analysis of Refractive Index Sensing Properties of a Hybrid Hollow Cylindrical Tetramer Array - Meng Wang; Paerhatijiang Tuersun; Aibibula Abudula; Lan Jiang; Dibo Xu (Nanomaterials)
In recent years, metal surface plasmon resonance sensors and dielectric guided-mode resonance sensors have attracted the attention of researchers. Metal sensors are sensitive to environmental disturbances but have high optical losses, while dielectric sensors have low losses but limited sensitivity. To overcome these limitations, hybrid resonance sensors that combine the advantages of metal and dielectric were proposed to achieve a high sensitivity and a high Q factor at the same time. In this paper, a hybrid hollow cylindrical tetramer array was designed, and the effects of the hole radius, external radius, height, period, incidence angle, and polarization angle of the hollow cylindrical tetramer array on the refractive index sensing properties were quantitatively analyzed using the finite difference time domain method. It is found that the position of the resonance peaks can be freely tuned in the visible and near-infrared regions, and a sensitivity of up to 542.8 nm/RIU can be achieved, with a Q factor of 1495.1 and a figure of merit of 1103.3 RIU−1. The hybrid metal–dielectric nanostructured array provides a possibility for the realization of high-performance sensing devices.